The Spirit of Purification in Indonesian Tafsir: T.M. Hasbi As-Siddieqy and His Interpretation of Verses on Tawasul in Tafsir An-Nur - Imanuddin, Imanuddin; Mursalim, Mursalim (An-Nida', 2024)
The Tafsir An-Nur by T.M. Hasbi As-Siddieqy (d. 1975) is one of the popular tafsir works in Indonesia. When interpreting the meaning of "wasilah" in Q.S. Al-Maidah [5]: 35, Hasbi tends to show a spirit of purification. However, the interpretation and historical context of this interpretation have not been widely analyzed. This article examines Hasbi's interpretation and its historical context by conducting a literature study of Tafsir An-Nur supported by various relevant literature. It is argued that Hasbi's interpretation in his tafsir is heavily influenced by certain contexts such as the scholarly and methodological context of tafsir, as well as the socio-cultural-religious conditions of his time. The results of this study reveal that Hasbi's interpretation of tawasul in this verse means drawing closer to Allah through good deeds and fear of Him. This interpretation differs from other mufassirs who interpret tawasul through the intermediary of pious people who are either still alive or have passed away. Furthermore, according to Hasbi, such tawasul was never practised by the Companions, whether during the life of the Prophet (PBUH) or after his death, either at the grave or elsewhere. According to him, such tawasul is not found in authentic evidence (dalil ma'tsur) and is only found in weak hadiths. Hasbi bases his interpretation on the opinions of jurists such as Imam Mālik, Abū Hanīfah, and asy-Syāfi’i. Using Hans-Georg Gadamer's hermeneutic theory, it is revealed that Hasbi's spirit of purification of religious understanding and practice, Hasbi's scholarly basis in the field of jurisprudence, and the tafsir methodology applied are some factors that contribute to influencing his interpretation.Abstrak: Tafsir An-Nur karya T.M. Hasbi As-Siddieqy (w. 1975) merupakan salah satu karya tafsir yang populer di Indonesia. Ketika menafsirkan makna wasilah dalam Q.S. Al-Maidah [5]: 35, Hasbi cenderung menunjukkan semangat purifikasi (pemurnian). Namun, penafsiran dan konteks historis dari penafsiran ini belum banyak dianalisis. Artikel ini mengkaji penafsiran Hasbi tersebut dan konteks historisnya, dengan melakukan studi literatur terhadap Tafsir An-Nur yang didukung oleh berbagai literatur yang relevan. Didasarkan pada argumen bahwa penafsiran Hasbi dalam tafsirnya sangat dipengaruhi oleh konteks-konteks tertentu seperti konteks keilmuan dan metodologi tafsir, serta kondisi sosial-budaya-keagamaan pada masanya. Hasil penelitian ini mengungkapkan bahwa penafsiran Hasbi tentang tawasul dalam ayat tersebut berarti mendekatkan diri kepada Allah melalui perbuatan baik dan rasa takut kepada-Nya. Penafsiran ini berbeda dengan mufasir lain yang menafsirkan tawasul melalui perantara orang-orang saleh yang masih hidup atau yang sudah meninggal. Lebih lanjut menurut Hasbi, tawasul semacam seperti itu tidak pernah dilakukan oleh Sahabat, baik semasa Nabi Saw masih hidup maupun sesudah wafat, ketika berada di kubur maupun di tempat lain. Menurutnya, tawasul semacam ini tidak terdapat dalam dalil yang ma’tsūr, dan hanya terdapat dalam hadis-hadis lemah. Hasbi mendasarkan penafsirannya ini pada pendapat ulama fikih seperti Imam Mālik, Abū Hanīfah, dan asy-Syāfi’i. Dengan menggunakan teori hermeneutika Hans-Georg Gadamer, terungkap bahwa semangat pemurnian Hasbi terhadap pemahaman dan praktik keagamaan, basis keilmuan Hasbi di bidang fikih, dan metodologi tafsir yang diterapkan adalah beberapa faktor yang bekonstribusi dalam mempengaruhi penafsirannya tersebut.